2020
DOI: 10.1016/j.apm.2020.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pollutant source location on air pollutant dispersion around a high-rise building

Abstract: a b s t r a c tThis article investigates the dispersion of airborne pollutants emitted from different locations near a high-rise building. A Computational Fluid Dynamics (CFD) model for simulating the wind flow field and the pollutant dispersion was developed and validated by wind tunnel data. Then the spreading of the pollutant emitted from different locations to a rectangular-shaped high-rise residential (HRR) building was numerically studied. The pollutant source location was set in a wide range of the posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…These studies concluded that the effect of high concentration air pollutants may last for days or week (Cirera et al, 2012;Glick et al, 2019;Hendryx et al, 2019;Hu et al, 2020;Huang et al, 2017;Kersen et al, 2020;Peng et al, 2019;Su et al, 2019). Qi et al, 2019 suggested that meteorological parameters have significant effects on dispersion, dilution and diffusion of air pollutants which ultimately affect the distribution, condensation and concentration of pollutants (Keshavarzian et al, 2020;Lim et al, 2020;Xiaoping Liu et al, 2019;Saha et al, 2018;Tiwari and Kumar, 2020;Junhua Yang et al, 2020;. However, there is an incubation period of 5 to 14 days to show the symptoms of COVID-19 infections as reported by the World Health…”
Section: Discussionmentioning
confidence: 97%
“…These studies concluded that the effect of high concentration air pollutants may last for days or week (Cirera et al, 2012;Glick et al, 2019;Hendryx et al, 2019;Hu et al, 2020;Huang et al, 2017;Kersen et al, 2020;Peng et al, 2019;Su et al, 2019). Qi et al, 2019 suggested that meteorological parameters have significant effects on dispersion, dilution and diffusion of air pollutants which ultimately affect the distribution, condensation and concentration of pollutants (Keshavarzian et al, 2020;Lim et al, 2020;Xiaoping Liu et al, 2019;Saha et al, 2018;Tiwari and Kumar, 2020;Junhua Yang et al, 2020;. However, there is an incubation period of 5 to 14 days to show the symptoms of COVID-19 infections as reported by the World Health…”
Section: Discussionmentioning
confidence: 97%
“…Expansion of urbanization leads to the dry-island effect [58], which results in more obvious vertical gradient of atmospheric humidity over cities (drier at the lower levels and wetter at the upper levels) [59], thus affecting urban precipitation. Wind affects urban heat dissipation and pollutant diffusion, among other factors [60]. NDVI, which denotes the growth potential of vegetation, and TREE, which stands for urban forest coverage, together represent the transpiration of vegetation, which has an important influence on changes in atmospheric relative humidity and surface temperature [61].…”
Section: Selection Of Variablesmentioning
confidence: 99%
“…Whenever obstacles (buildings, trees or hills) are involved, a building influence area (BIA) concept is adopted (Keshavarzian et al, 2020;Longo et al, 2017). The latter permits to automatically detect the obstacle through a deviation parameter ÎŽ, estimating the relative error between homogeneous ABL conditions and the local values of relevant turbulence parameters Longo et al (2020b), as described in Table 2.…”
Section: Inlet Conditions Turbulence Modelmentioning
confidence: 99%